2014
DOI: 10.1186/s12865-014-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mTOR inhibitor Rapamycin on Monocyte-Secreted Chemokines

Abstract: BackgroundMammalian target of rapamycin (mTOR) inhibitors, such as sirolimus and its derivative, everolimus, are potent immunosuppressive and antiproliferative drugs. Inflammatory diseases are characterized by immunological dysfunction, and monocyte recruitment underlies the mechanism of cell damage. Chemokines attract inflammatory cells to sites of inflammation. Interleukin-8 (IL-8/CXCL8); the monocyte chemoattractant protein-1 (MCP-1/CCL2); the regulated on activation, normal T cell expressed, presumably sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 45 publications
1
42
1
2
Order By: Relevance
“…The inhibition of mTOR markedly ameliorated macrophage infiltrates, tubular injuries and fibrosis, which may work through a suppression of inflammatory chemokines in macrophages. These findings are in agreement with previous reports that LPS could induce an abundant expression of chemokines in macrophages through the activation of mTOR signaling, which could be significantly suppressed by rapamycin [36,37] . It will be challenging to further explore the role of mTOR in macrophage dynamics and its correlation with outcomes of kidney disease.…”
Section: Discussionsupporting
confidence: 83%
“…The inhibition of mTOR markedly ameliorated macrophage infiltrates, tubular injuries and fibrosis, which may work through a suppression of inflammatory chemokines in macrophages. These findings are in agreement with previous reports that LPS could induce an abundant expression of chemokines in macrophages through the activation of mTOR signaling, which could be significantly suppressed by rapamycin [36,37] . It will be challenging to further explore the role of mTOR in macrophage dynamics and its correlation with outcomes of kidney disease.…”
Section: Discussionsupporting
confidence: 83%
“…34 Our data showed that LPS induced IL1β, IL6, TNFα, and MCP1 in THP1-derived macrophages after 24 and 48 hours' stimulation, in concordance with other studies that showed a minor variation due to the activation duration and LPS concentration used. [35][36][37] As in the case of monocytes, treatment of macrophages with Lipo/GOT significantly decreased the production of cytokines IL1β, IL6, TNFα, and MCP1 induced by LPS activation compared with free GOT, which showed no effect on the secretion of cytokines in the conditioned media of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expressing CCR2 and CCR5, macrophages secret a set of chemokines which affect angiogenesis and wound healing. It was reported that Rapamycin (Rapa, an inhibitor of mTORC1) suppressed the expression of CCL2, CXCL8, CCL5, CCL8 and CCL4 in the THP-1 cells induced by LPS and human primary monocytes [14]. The stimulated production of reactive oxygen species (ROS) by phagocytic cells is necessary for the bactericidal action of phagocytes [15].…”
Section: Introductionmentioning
confidence: 99%